Arrow C-106 Engine Performance Analysis Based on Mean Time Between Failure (MTBF) Mean Time To Repair (MTTR) and Availability Methods at PT. Pertamina Hulu Rokan Regional 1 Zone 1 Field Rantau - Yasir Amani Yasir Amani; Ade Ariansyah Ritonga; M.Iqbal A.Putra Putra; Faisal Muhammad Nur; Heindrix Hidayat (Journal of Mechafa Engineering and Fabrication, 2026)
Through data collection and analysis of the performance of the Arrow C-106 Engine at PT Pertamina Hulu Rokan's Rantau Field. The results of the analysis are expected to provide an overview of the actual condition of the machine, its level of reliability, and its availability to support the oil and gas production process. The data analysis method in this research was carried out by processing Arrow C-106 Engine operational data obtained from log sheets, downtime records and company documentation. The data that has been collected is then calculated using three main parameters, namely MTBF, MTTR, and Availability. The results of the analysis of these three parameters are then compared with actual conditions in the field, in order to obtain an overview of the reliability and availability of the Arrow C-106 engine in supporting oil and gas production operations. Mean Time Between Failure (MTBF) shows that the Arrow C-106 Engine has the ability to operate for a relatively long duration before damage occurs. The Mean Time To Repair (MTTR) value obtained is relatively small, so the average repair time required is not too long. The calculated Availability parameters for individual units are in the high range, with most units recording values ​​above 95%. This high level of availability shows that the Arrow C-106 Engine has good operational readiness and can be relied on to support the continuity of oil and gas production.